Sobrepeso y su relación con el consumo de alimentos procesados en estudiantes de la Escuela Teniente Hugo Ortiz de Loja - Hidalgo Soto, Ximena Alejandra (2019)
Overweight is a disease that is characterized by the increase in body weight above the values that are considered normal or acceptable (imc = 18.5-24.9), with children, adolescents and young people being the most affected. It attributes to the current socioeconomic changes that have led parents and children to consume inadequate food. For this reason, the purpose of this research work was to evaluate the relationship between overweight and the consumption of processed foods in students from the fourth to seventh year of General Basic Education of the Teniente Hugo Ortiz de Loja school in the academic period October 2018 - March 2019. This is a quantitative, descriptive, correlational and cross-sectional study, the technique used was the survey applied to a sample of 173 schoolchildren, obtaining the following results; 37.6% of the students were overweight; the highest proportion was in the female sex with 21.4%, in ages between 10 and 11 years. It was determined that 89.9% of students consume the highest amount of processed foods in school and only 12.2% consume them at home. It was also identified that there is a relationship between overweight and consumption of processed foods, with high fat products being part of the intake of students, followed by those with a high content of sugar and salt. Keywords: Children, Products, Body weight